Kinerja Pelayanan Publik dan Indeks Pelayanan Publik (IPP): Konsep, Dasar Hukum, dan Indikator Pengukuran - Sri Yuliyanti Mozin; Sri Naila Putri Abdullah; Alya Putri Pantoiyo; Nur Afni Zakaria; Rahmi Thaib (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Public service performance serves as a crucial measure of how effectively government agencies provide services to the public. Rising expectations from the public compel governments to ensure that services are delivered in an efficient, open, responsible, and responsive manner. Within the realm of public administration reform, the standard of public services has emerged as a key issue for governments looking to enhance public confidence and governance. The Indonesian government has created the Public Service Index (Indeks Pelayanan Publik/IPP) as a tool to assess the performance of public services. The IPP functions as an all-encompassing measurement system to evaluate the quality, efficiency, and responsibility associated with public service provision across government entities. This research intends to explore the definition of public service performance, the legal framework that regulates public services in Indonesia, and the metrics employed for calculating the Public Service Index. The study uses a qualitative descriptive method and a literature review approach, evaluating various pertinent books, regulations, and scholarly articles concentrating on public service management and performance evaluation. The results indicate that the Public Service Index plays a vital role in assessing service quality, institutional effectiveness, and the degree of public satisfaction. Additionally, the application of the IPP measurements fosters transparency, bolsters accountability, and encourages ongoing enhancements in public service delivery. Therefore, enhancing public service performance necessitates robust regulatory backing, institutional dedication, and the utilization of clear and quantifiable performance metrics to guarantee enduring improvements in service quality.